1976
DOI: 10.1246/cl.1976.655
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Catalytic Reduction of Aromatic Nitro-Compounds by Hydrogen Transfer

Abstract: In the presence of noble metal salts, indoline reduced aromatic nitro-compounds to the corresponding aromatic amines under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Alternatively, nitroarene compounds can be reduced to aromatic amines by "extracting" hydrogen from hydrogen-donor molecules, that is, transfer hydrogenation. [14][15][16][17][18][19][20] Among the available hydrogen donors, [21][22][23] FA, which may be derived from biomass with low toxicity and high stability, is an abundant and cheap hydrogen source for safe hydrogen usage and storage. [24][25][26] The only byproduct of dehydrogenation reaction of FA, CO 2 , could be regenerated to FA by chemical or biological routes in large quantities, [24,25] completing the sustainable cycles for the potential use of FA as hydrogen source.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, nitroarene compounds can be reduced to aromatic amines by "extracting" hydrogen from hydrogen-donor molecules, that is, transfer hydrogenation. [14][15][16][17][18][19][20] Among the available hydrogen donors, [21][22][23] FA, which may be derived from biomass with low toxicity and high stability, is an abundant and cheap hydrogen source for safe hydrogen usage and storage. [24][25][26] The only byproduct of dehydrogenation reaction of FA, CO 2 , could be regenerated to FA by chemical or biological routes in large quantities, [24,25] completing the sustainable cycles for the potential use of FA as hydrogen source.…”
Section: Introductionmentioning
confidence: 99%
“…[4] A crucial issue for the general application of catalysts for nitro reduction is selectivity. [7,8] Hence, a wide variety of organometallic catalysts based on Pd, [7] Ru, [7][8][9] Rh, [7] Co, [10] Cu, [10] and even Fe [11] have been described. Recently, Corma and co-workers demonstrated that Au-based catalysts show high selectivity for the reduction of the nitro arenes.…”
mentioning
confidence: 99%
“…Nitroarene (1) is hydrogenated to nitrosoarene (5) by the iridium hydride complex and proton with release of one molecular water. [6d,23] Then a sequent hydrogenation of 5 leads to hydroxylamine (6), which under-goes a followed hydrogenation with release of the second water to afford the desired arylamine (2, Path A). An equilibrium is existed between 2 and the condensation intermediate 4.…”
Section: Resultsmentioning
confidence: 99%
“…[2,3] On the other hand, the combinations of protons with hydride reagents or electron donors, and other in-situ generated hydrogen sources by hydrogen transformation were also well developed ( Figure 1B). [2,[4][5][6] Exploring of hydrogen source from renewable resource for direct hydrogenation reactions, such as glucose in alkaline solution, had been studied since 1860s ( Figure 1C). [7a] In these reactions, more than stoichiometric amounts of glucose and base were required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation